Box Behnken$1 (Bs Design of Fast-Dissolving Ondansetron Buccal Films and Assessing the Impact of Independent Variables on their Swelling and Folding Endurance Constraintss - Phaneendra Kurapati
The solvent casting method was used to make the films. Complex formation and compatibility were evaluated using spectral and calorimetric methods to confirm. Utilising the core composite design, which included 13 different Ondansetron Fast-Dissolving Oral Films (OFDOFs) formulas, the produced Ondansetron Fast-Dissolving Oral Films (OFDOFs) were optimised. Using the Design Expert-v.11 software, the impacts of three variables, including HPMC K4M (X1), Carbopol 934 P (X2), and propylene glycol levels (X3), on two responses, Folding Endurance (FE) and Swelling Index (SI), were examined. Numerical optimisation increased the FE (Y1) and maximised the SI (Y2).